Publication potential in pediatrics in Turkey - Tınaztepe, Keriman (The Turkish Journal of Pediatrics, 1996)
In this article, the publication potential in pediatrics in Turkey was investigated. In this context, native pediatric journals, publication activities of medical faculties as the main source of scientific publication and certain data obtained from some of the international Indexes’ sources were analyzed. The Turkish Journal of Pediatrics (Turk J Pediatr) and Çocuk Sağlığı ve Hastalıkları Dergisi are two native pediatric journals which have been published without interruption for 36 and 37 years, respectively. Both are indexed in BIOSIS (Bioscience Information Service) and Excerpta Medica. In addition, Turk J Pediatr is indexed in Index Medicus and Current Contents, and is the only Turkish medical journal indexed in Index Medicus at present. Eighty percent of papers submitted to both journals are from medical faculties all over the country (60% of these from Hacettepe Faculty of Medicine), while 15% are from the teaching hospitals of the Ministry of Health and 5% from outside the country. In 1994, Hacettepe University School of Medicine was the leader with 244 (21%) of the 1165 articles published in the health sciences from 22 medical faculties in Turkey. In the same year, 32 percent of all international medical publications by Hacettepe Faculty of Medicine were in the field of pediatrics. In addition, of 353 papers by Turkish authors appearing in Current Contents during the three-month period July-September 1993, 70 (20%) were pediatric articles. All of these findings may indicate that publications in the field of pediatrics have increasing potential and an important impact on the scientific medical publication’s platform in our country.
Keywords: scientific publication potentials; pediatrics; Turkish Journal of Pediatrics; Çocuk Sağlığı ve Hastalıkları Dergisi; Turkey